Childhood maltreatment affects depression and anxiety: The mediating role of benign envy and malicious envy - Li, Xiaojun; Tu, Linping; Jiang, Xinsheng (Frontiers in Psychiatry, 2022)
The influence of childhood maltreatment on depression and anxiety has been reported in many studies, and the mechanism of this influence has been described from different perspectives. However, few research has explored the influence of child maltreatment on depression and anxiety from the perspective of benign/malicious envy. Given that, based on social comparison theory, this study explored the mediating effect of benign envy/malicious envy on child maltreatment, depression, and anxiety. The sample of this study consisted of 2,691 Chinese adolescents. The results showed that benign and malicious envy both played a significant role in mediating the relation between childhood maltreatment and depression and anxiety. Interestingly, we found that there were different mechanisms of benign and malicious envy in this relationship, namely, malicious envy promoted the effects of childhood maltreatment on depression and anxiety, whereas benign envy inhibited the effects of childhood maltreatment on depression and anxiety. These findings not only reveal the different mechanisms between the two socially comparable emotions of benign/malicious envy in the early adverse environment and depression and anxiety, but also provide a specific reference for individuals to regulate the depression and anxiety caused by childhood maltreatment and envy.